The VEGF and PEDF levels in the follicular fluid of patients co- treated with LETROZOLE and gonadotropins during the stimulation cycle - Jigal Haas; Rawad Bassil; Noa Gonen; Jim Meriano; Andrea Jurisicova; Robert F. Casper (BMC, 2018)
Abstract Background Previous studies have shown that androgens, in addition to serving as precursors for ovarian estrogen synthesis, also have a fundamental role in primate ovarian follicular development by augmentation of FSH receptor expression on granulosa cells. Recent studies have shown that aromatase inhibitor, letrozole, improves ovarian response to FSH in normal and poor responder patients, possibly by increasing intraovarian androgen levels. Studies in mice also showed an effect of letrozole to increase pigment epithelium-derived factor (PEDF) and to lower vascular epithelial growth factor (VEGF), which might be expected to reduce the risk of ovarian hyperstimulation syndrome (OHSS) with stimulation. The aim of this study was to compare the VEGF and PEDF levels in the follicular fluids of normal responders treated with letrozole and gonadotropins during the ovarian stimulation with patients treated with gonadotropins only. Methods A single center, prospective clinical trial. We collected follicular fluid from 26 patients, on a GnRH antagonist protocol, dual triggered with hCG and GnRH agonist. The patients in one group were co-treated with letrozole and gonadotropins during the ovarian stimulation and the patients in the other group were treated with gonadotropins only. VEGF, PEDF, estrogen, progesterone and testosterone levels were measured by ELISA kits. Results The age of the patients, the total dose of gonadotropins and the number of oocytes were comparable between the two groups. In the follicular fluid, the estrogen levels (2209 nmol/l vs. 3280 nmol/l, p = 0.02) were significantly decreased, and the testosterone levels (246.5 nmol/l vs. 40.7 nmol/l, p < 0.001) were significantly increased in the letrozole group compared to the gonadotropin only group. The progesterone levels (21.4 μmol/l vs. 17.5 p = NS) were comparable between the two groups. The VEGF levels (2992 pg/ml vs. 1812 pg/ml p = 0.02) were significantly increased and the PEDF levels (9.7 ng/ml vs 17.3 ng/ml p < 0.001) were significantly decreased in the letrozole group. Conclusions Opposite to observations in the mouse, we found that VEGF levels were increased and PEDF levels were decreased in the follicular fluid in patients treated with letrozole during the stimulation cycles. Further investigation is required to determine if patients treated with letrozole during the IVF stimulation protocol are at increased risk for developing OHSS as a result of these findings.